Pengembangan Media Pembelajaran Geografi StoryMaps Untuk Meningkatkan Kemampuan Berpikir Spasial Peserta Didik SMA - Nadliva Mukammilah Qolbi; Yusuf Suharto; Tuti Mutia; I Komang Astina; Noenoek Noerhajati (Jayapangus Press, 2026)
In geography education in Indonesia, students' spatial thinking skills are generally assessed as still low due to the limited application of spatial approaches, both in the form of learning activities and the utilization of media in instruction. This study aims to develop StoryMaps as an innovative instructional media that integrates geospatial narrative maps to enhance students' spatial thinking abilities on the topic of flora and fauna distribution. A Research and Development (R&D) approach using the ADDIE framework which encompasses Analysis, Design, Development, Implementation, and Evaluation was employed in this study to develop and validate the product. The research findings indicate that the intervention of StoryMaps media in geography learning results in differences in students' spatial thinking skill levels. This condition is evident from the post-test scores of spatial thinking skills in both classes, which showed a difference of 6.03%, with the experimental class average outperforming the control class by 5.32 points. Pedagogically, this reflects a stronger impetus for deeper spatial concept understanding and sustained knowledge retention through the application of StoryMaps instructional media. Based on these results, it can be concluded that the use of StoryMaps media effectively improves students' spatial understanding of the taught geography material. Through the development of this instructional media, it is expected that students will gain more engaging and realistic experiences, thereby enhancing their motivation and comprehension of the learning material.